Peran Supervisi Pendidikan Dalam Pengembangan Profesionalisme Guru PAI Di SMP Negeri 1 Padangsidimpuan - Irda Suriani; Sahdin Tambunan (Journal of Innovative and Creativity, 2025)
Educational supervision is one of the strategic efforts to improve the quality of learning and teacher professionalism. The background of this research arises from the fact that Islamic Religious Education (PAI) teachers at SMP Negeri 1 Padangsidimpuan still face challenges in mastering learning strategies, utilizing media, and developing themselves continuously. The main problem examined in this study is the extent to which educational supervision plays a role in encouraging the professional development of PAI teachers at the school. This research aims to identify the role of educational supervision in the aspects of planning, implementation, and evaluation of learning, as well as its impact on improving the professional competence of PAI teachers. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The findings show that educational supervision conducted by the principal and supervisors plays an important role in guiding PAI teachers. Collaborative and communicative supervision improves teachers’ abilities in designing lesson plans, managing classrooms, and applying various teaching methods according to students’ needs. In addition, supervision also encourages teachers to be more active in self- development activities, such as training programs and Teacher Working Group (MGMP) forums. The conclusion of this study is that educational supervision not only functions as monitoring but also as effective professional mentoring. Through well-directed supervision, PAI teachers at SMP Negeri 1 Padangsidimpuan experience improvements in pedagogical, professional, and social competencies, which positively affect the quality of Islamic Religious Education learning at the school.